Effects of parents' attachment styles and attention deficit symptoms on social responsiveness in children with ADHD - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2019)
Objective: The aim of this study is to investigate the effects of parental attachment styles and parental inattentiveness symptoms on social responsiveness problem scores of school age children diagnosed with attention deficit hyperactivity disorder (ADHD). Methods: One hundred and seventy-nine children with ADHD diagnosed between 7 and 12 years and their parents were the sample of the study. The Schedule for Affective Disorders and Schizophrenia for School-Age Children - Present and Lifetime Version was used to determine the presence of psychiatric disorders in the children. Parents were asked to fill out the Parental Attachment Scale, Wender Utah Rating Scale, and Social Responsiveness Scale. Results: As a result of the path analysis, it was shown that avoidant and ambivalent attachment levels of mothers had a significant increase effect on the levels of social responsiveness of children and mothers' attention deficit symptoms mediated this effect. The attachment style scores of fathers were not correlated with social responsiveness of children. Conclusion: In children with attention deficit hyperactivity disorder comorbid with social responsiveness problems, it is recommended to consider the attachment patterns of parents, especially mothers, and possible attention deficit symptoms.
Keywords: child; attention deficit hyperactivity disorder; parental attachment style; social responsiveness; SCHOOL-AGE-CHILDREN; UTAH RATING-SCALE; DEFICIT/HYPERACTIVITY DISORDER; AUTISTIC TRAITS; RELIABILITY; VALIDITY; VERSION